ANALISIS SENSORI ES PUTER SUBTITUSI KULIT PISANG KEPOK DAN BIJI CHIA SEBAGAI PRODUK TINGGI SERAT DAN RENDAH LEMAK - Talitha Sahda Nathaniela; Rita Ismawati (JOURNAL HEALTH AND NUTRITIONS, 2023)
Obesity is a nutritional problem with a prevalence that continues to increase from year to year. One of the efforts to prevent obesity is through the implementation of balanced nutrition guidelines by consuming lots of fiber sources and limiting high-fat intake. The purpose of this study was to develop a product in the form of ice puter substituted with banana peel with the addition of chia seeds to be sensorially evaluated by looking at differences in the level of liking for color, aroma, texture, taste and overall and analyzing fiber and fat content in ice puter formulations with a ratio of banana peel and chia seeds (30%; 50%) and (20g; 10g). This research is an experimental study using a 2x2 factorial completely randomized design (CRD). Sensory test research subjects were 30 panelists. The analisys data were using the Kruskall Wallis Test followed by the Mann Whitney Test. The results of the study based on the results of statistical tests showed that there were significant differences in the parameters of color, aroma, texture, taste and overall (p<0.05). Substitution of kepok banana peel and the addition of chia seeds influenced the level of panelists' liking and affected the fiber and fat content of es puter. Obesitas merupakan masalah gizi dengan prevalensi yang terus mengalami peningkatan dari tahun ke tahun. Salah satu upaya untuk pencegahan obesitas adalah melalui penerapan pedoman gizi seimbang dengan banyak mengkonsumsi sumber serat serta membatasi asupan tinggi lemak. Tujuan dari penelitian ini adalah mengembangkan produk berupa es puter yang disubtitusikan kulit pisang dengan penambahan biji chia untuk dievaluasi secara sensori dengan melihat perbedaan tingkat kesukaan warna, aroma, tekstur, rasa dan keseluruhan serta menganalisis kadar serat dan lemak pada formulasi es puter dengan perbandingan kulit pisang dan biji chia (30%;50%) dan (20g;10g). Penelitian ini merupakan penelitian eksperimen dengan menggunakan Rancangan Acak Lengkap (RAL) faktorial 2x2. Subjek penelitian uji sensori sebanyak 30 orang panelis. Data dianalisis menggunakan Uji Kruskall Wallis dilanjutkan dengan Uji Mann Whitney. Hasil penelitian berdasarkan hasil uji statistik menunjukkan bahwa terdapat perbedaan yang signifikan pada parameter warna, aroma, tekstur, rasa dan keseluruhan (p< 0.05). Subtitusi kulit pisang kepok dan penambahan biji chia memberikan pengaruh pada tingkat kesukaan panelis serta mempengaruhi kandungan serat dan lemak pada es puter.